Socially Shared Feelings of Imminent Recall: More Tip-of-the-Tongue States Are Experienced in Small Groups - Rousseau, Luc; Kashur, Nathalie (Frontiers in Psychology, 2021)
Tip-of-the-tongue (TOT) states are typically defined as feelings of imminent recall for known, but temporarily inaccessible target words. However, TOTs are not merely instances of retrieval failures. Clues that increase the subjective likelihood of retrieval success, such as cue familiarity and target-related information, also have been shown to elicit feelings of imminent recall, supporting a metacognitive, inferential etiology of the TOT phenomenon. A survey conducted on our university campus provided anecdotal evidence that TOTs are occasionally shared among people in small groups. Although shared TOTs may suggest the influence of social contagion, we hypothesized that metacognitive appraisal of group recall efficiency could be involved. There should be more instances of remembering in several heads than in one. From this, we conjectured that people remembering together entertain the inference that successful retrieval is more likely in group recall than in a single-person recall situation. Such a metacognitive appraisal may drive a stronger feeling of closeness with the target word and of recall imminence, precipitating one (or more people) into a TOT state. We used general knowledge questions to elicit TOTs. We found that participants reported more TOTs when remembering in small groups than participants remembering alone. Critically, the experimental manipulation selectively increased TOTs without affecting correct recall, suggesting that additional TOTs observed in small groups were triggered independently from the retrieval process. Near one third (31%) of the TOTs in small groups were reported by two or more participants for the same items. However, removing common TOTs from the analyses did not change the basic pattern of results, suggesting that social contagion was not the main factor involved in the observed effect. We argue that beyond social contagion, group recall magnifies the inference that target words will be successfully retrieved, prompting the metacognitive monitoring system to launch more near-retrieval success “warning” (TOT) signals than in a single-person recall situation.